2023
DOI: 10.1186/s13014-023-02266-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a simultaneously integrated boost concept for hypofractionated stereotactic radiotherapy of unresected brain metastases

Christine Kornhuber,
Stephan Ensminger,
Patrick Hübsch
et al.

Abstract: Background In stereotactic radiotherapy, dose is prescribed to an isodose surrounding the planning target volume (PTV). However, the desired dose inhomogeneity inside the PTV leaves the specific dose distribution to the gross tumor volume (GTV) unspecified. A simultaneously integrated boost (SIB) to the GTV could solve this shortcoming. In a retrospective planning study with 20 unresected brain metastases, a SIB approach was tested against the classical prescription. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Multifraction SRT treatments were also recently reported by Kornhuber et al [40] from a physicist perspective, with the aim of delivering a more homogeneous dose to the GTV, with a simultaneous integrated boost (SIB) approach. Starting from a five-fraction prescription with a total dose of 35 Gy to the PTV, the authors suggested the potential favorable impact of this approach as a means to reducing the risk of radiation necrosis.…”
Section: Discussionmentioning
confidence: 98%
“…Multifraction SRT treatments were also recently reported by Kornhuber et al [40] from a physicist perspective, with the aim of delivering a more homogeneous dose to the GTV, with a simultaneous integrated boost (SIB) approach. Starting from a five-fraction prescription with a total dose of 35 Gy to the PTV, the authors suggested the potential favorable impact of this approach as a means to reducing the risk of radiation necrosis.…”
Section: Discussionmentioning
confidence: 98%